Evaluasi Efektivitas Program PFmuda Pertamina Foundation Terhadap Kebermanfaatan dan Keberlanjutan Usaha Peserta - Kirana Rahayu Widyadhani; Hasyim Asy’ari (LPPM Politeknik Pratama, 2026)
This study aims to evaluate the effectiveness of the PFmuda Program by Pertamina Foundation in supporting the development and sustainability of micro, small, and medium enterprises (MSMEs). The research focuses on analyzing the influence of funding, mentoring, training, business networking, and business sustainability on participants’ perceived program benefits. A quantitative approach was employed by distributing questionnaires to 87 PFmuda alumni selected through purposive sampling. The results show that all independent variables have a positive and significant partial effect on the program’s perceived usefulness, with t-values of 4.907 (funding), 3.096 (mentoring), 2.033 (training), 2.178 (business networking), and 2.524 (business sustainability), at a significance level of < 0.05. The simultaneous test also indicates a significant effect, with an F-value of 42.629 (p = 0.000). The model yields a coefficient of determination of adjust R² = 0.708, indicating that 70.8% of the variation in program benefits is explained by the tested variables. These findings confirm that PFmuda contributes to enhancing the entrepreneurial capacity and competitiveness of its alumni, although challenges related to post-program business sustainability remain. The study recommends strengthening post-program support and expanding market access to better ensure long-term MSME sustainability